Utilization of Banana Leaf Fiber as a Material for Making False Eyelashes - Vivi Efrianova; Samul Martin Pradana; Nabilla Yasmin; Aulia Khairani; Edi Syafri (Green Engineering Society, 2025)
False eyelashes are essential tools used to enhance the appearance of the eyes in makeup application. However, most variants of false eyelashes currently available on the market are made from human hair and synthetic materials, which do not guarantee halal quality for Muslim consumers. This study aims to develop a new variant of false eyelashes made from halal-certified natural fibers. The false eyelashes are produced using natural fibers derived from the leaf sheaths of Musa paradisiaca (kepok banana), Musa textilis (abaca banana), and Musa sapientum (ambon banana), which are mechanically processed and crafted using a hanging netting technique, with designs adjusted to fit the shape of the eyes. Based on laboratory tests for tensile strength and modulus of elasticity, abaca banana fibers achieved the highest values at 72.49 g/tex and 1.85 g/tex, respectively. For fiber smoothness testing, kepok banana fibers scored the highest at 10.44 g/tex. In organoleptic tests, abaca banana fibers received the highest score for curliness at 66.7%; for lightness, both kepok and abaca banana fibers shared the highest score at 44.4%; and for neatness, kepok and abaca banana fibers again shared the highest score at 66.7%. In hedonic preference tests, kepok banana fibers scored 44.4%, abaca 50%, and ambon 60%. It can be concluded that false eyelashes made from the leaf sheath fibers of kepok, abaca, and ambon bananas are considered visually suitable for use in makeup based on organoleptic and hedonic evaluations. The results of this study contribute to the development of new variants of halal-certified false eyelashes in the cosmetic industry.